Religiosity/spirituality in mental health contexts: Brazilian production in the last ten years (Phenomenology, Humanities and Sciences, 2025)
This article describes a systematic review of the Brazilian literature concerning the relationships between Religiosity and Spirituality (RS) and mental health (MH), primarily focusing on articles published in the last 10 years. Searches in the SciELO, BVS, PePSIC, and CAPES bases (January 2012 and /October 2023) retrieved 89 eighty-nine scientific productions, mostly empirical and qualitative. Besides to the meta-analysis, content analysis of the selected articles was also performed, distributing them into ten thematic groups according to how RS appeared associated with MH. Spirituality was the most addressed concept, followed by religiosity and religion. It was evident that RS has been incorporated into health notions and understood in MH care as having a positive impact, promoting well-being and a sense of life. For mental health professionals themselves, RS has been a coping/ facing strategy in their personal and professional daily lives. It is concluded that this topic should be included in the psychology’s degree training and related areas.